Octahedron-based gallium borates (Ga-PKU-1) with an open framework: acidity, catalytic dehydration and structure–activity relationship. Issue 15 (6th May 2016) - Wang, Guangjia; Wang, Weilu; Zhang, Fenhua; Gao, Wenliang; Cong, Rihong; Yang, Tao
Abstract : The octahedron-based Ga-PKU-1 catalyst with an open framework acted as an efficient solid acid catalyst for isopropanol decomposition. Abstract : An octahedron-based gallium borate (Ga-PKU-1) with an open framework was prepared by the boric acid flux method and studied by XRD, SEM, FT-IR, TGA-DSC, BET and NH3 -TPD. The borate hydroxyl groups in the 18-ring membered channels functioned as Brönsted acid centers and were proved to play an important role in the dehydration of isopropanol to propylene with high selectivity. However, the other two gallium borates, Ga4 B2 O9 and GaBO3, with similar elemental compositions showed completely different acidities and catalytic performance for isopropanol decomposition. Our results indicated that such a great difference in selectivity most probably originated from the changes in the coordination microenvironment from GaO6 to GaO5 . The relationship between the structure and activity was discussed in detail, and an intrinsic mechanism for the selectivity preference was proposed according to the obtained results.